Three Transcription Activators of ABA Signaling Positively Regulate Suberin Monomer Synthesis by Activating Cytochrome P450 CYP86A1 in Kiwifruit - Wei, Xiaopeng; Mao, Linchun; Lu, Wenjing; Wei, Xiaobo; Han, Xueyuan; Guan, Weiliang; Yang, Yajie; Zha, Meng; Xu, Changjie; Luo, Zisheng (Frontiers in Plant Science, 2020)
Wound attack stimulates accumulation of abscisic acid (ABA) that activates a number of genes associated with wound suberization of plants. Cytochrome P450 fatty acid ω-hydroxylase CYP86A1 catalyzes ω-hydroxylation of fatty acids to form the ω-functionalized monomers that play a pivotal role in suberin synthesis. However, the transcriptional regulation of ABA signaling on AchnCYP86A1 has not been characterized in kiwifruit. In this study, AchnCYP86A1, a kiwifruit homolog of Arabidopsis AtCYP86A1, was isolated. AchnCYP86A1-overexpressed N. benthamiana leaves displayed that the AchnCYP86A1 functioned as a fatty acid ω-hydroxylase associated with synthesis of suberin monomer. The regulatory function of three transcription factors (TFs, including AchnMYC2, AchnMYB41 and AchnMYB107) on AchnCYP86A1 was identified. All the three TFs were localized in nucleus and could individually interact with AchnCYP86A1 promoter to activate gene expression in yeast one-hybrid and dual-luciferase assays. The findings were further demonstrated in transient overexpressed N. benthamiana, in which all TFs notably elevated the expression of aliphatic synthesis genes including CYP86A1 and the accumulation of ω-hydroxyacids, α, ω-diacids, fatty acids and primary alcohols. Moreover, exogenous ABA induced the expression of AchnMYC2, AchnMYB41 and AchnMYB107 that promoted AchnCYP86A1 involving in suberin monomer formation. Contrary to the inductive effects of ABA, however, fluridone (an inhibitor of ABA biosynthesis) inhibited the three TFs expression and suberin monomer formation. These results indicate that AchnMYC2, AchnMYB41 and AchnMYB107 positively regulate suberin monomer synthesis by activating AchnCYP86A1 promoter in response to ABA.